Kierunki ewolucji Unii Europejskiej na tle wyzwań globalnych - Mikiewicz, Przemysław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The aim of the author is to present the possible consequences of any further intensification of the global problems which the European Union will have to stand up to, to a larger degree than before. Globalization has not created global problems, but it has contributed to their intensification. There are four groups of global issues that are of particular significance to globalization processes: (1) international security, (2) ecology, (3) demography, and (4) poverty and marginalization. Undoubtedly, the European Union is a ‘privileged’ region as it comprises safe states. Europe and the United States perceive the prevention of threats to be a common interest, which justifies the claim that the two partners are at least partially chained to each other. However, Europe is vulnerable to the consequences of global threats. In future, poor countries will blame developed countries for their problems, including those related to their natural environment. Adverse demographic trends will result in the European population growing older and there will be a decrease in the numbers of native Europeans. International relations may be destabilized in the long-term by the widening gap between the developed countries and developing ones, and by their feelings of being excluded from globalization processes. An alternative to this scenario could be provided by cohesive and active global policies on the part of the EU, however, it cannot change the adverse consequences of modern global trends by itself.